2006
DOI: 10.5194/bg-3-621-2006
|View full text |Cite
|
Sign up to set email alerts
|

Coastal versus open-ocean denitrification in the Arabian Sea

Abstract: Abstract. The Arabian Sea contains one of the three major open-ocean denitrification zones in the world. In addition, pelagic denitrification also occurs over the inner and midshelf off the west coast of India. The major differences between the two environments are highlighted using the available data. The perennial open-ocean system occupies two orders of magnitude larger volume than the seasonal coastal system, however, the latter offers more extreme conditions (greater nitrate consumption leading to complet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
132
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 59 publications
(68 reference statements)
16
132
2
Order By: Relevance
“…Lower bottom-water oxygen levels result in less oxidation of particulate and dissolved reduced sulphur compounds with the result that more reduced sulphur is buried (high sulphide retention efficiency; Canfield, 1994;Passier et al, 1997) and that sulphide may escape from the sediments to the water column (Brüchert et al, 2003;Lavik et al, 2009). Hydrogen sulphide release from anoxic sediments has been reported for permanently anoxic systems such as the Black Sea and Cariaco basin as well as for more dynamic settings experiencing hydrogen-sulphide release events (Namibian coastal upwelling, Brüchert et al, 2003, Lavik et al, 2009; the Indian shelf, Naqvi et al, 2006). Recently, Lavik et al (2009) reported detoxification of sulphidic waters from the Namibian shelf by chemolithotrophs (of the γ -and β-proteobacteria) in the water column that completely consumed the sulphide and created a buffer zone between toxic, sulphidic subsurface waters and oxic surface waters.…”
Section: The Effect Of Oxygen On Diagenetic Pathways and Sediment-watmentioning
confidence: 99%
“…Lower bottom-water oxygen levels result in less oxidation of particulate and dissolved reduced sulphur compounds with the result that more reduced sulphur is buried (high sulphide retention efficiency; Canfield, 1994;Passier et al, 1997) and that sulphide may escape from the sediments to the water column (Brüchert et al, 2003;Lavik et al, 2009). Hydrogen sulphide release from anoxic sediments has been reported for permanently anoxic systems such as the Black Sea and Cariaco basin as well as for more dynamic settings experiencing hydrogen-sulphide release events (Namibian coastal upwelling, Brüchert et al, 2003, Lavik et al, 2009; the Indian shelf, Naqvi et al, 2006). Recently, Lavik et al (2009) reported detoxification of sulphidic waters from the Namibian shelf by chemolithotrophs (of the γ -and β-proteobacteria) in the water column that completely consumed the sulphide and created a buffer zone between toxic, sulphidic subsurface waters and oxic surface waters.…”
Section: The Effect Of Oxygen On Diagenetic Pathways and Sediment-watmentioning
confidence: 99%
“…It is important to note the distinct decline of nitrates in the central Arabian Sea, which is within core of the perennial denitrification zone, indicative of enhanced utilization of nitrates due to intensification of denitrification. The nutrient and DO depth profiles of the central Arabian Sea are known to be governed by the availability of nutrients from subsurface waters of adjacent productive zones of the eastern and western Arabian Sea, even though the open-ocean and coastal suboxic zones are not contiguous (Naqvi et al 2006). Hence, enhanced productivity, and thereby intensification of denitrification, in adjacent productive zones can be expected to leave their imprint in intermediate to deeper water nitrate contents of the central Arabian Sea as well.…”
Section: Changes In Nutrients (Nitrates Phosphates and Silicates)mentioning
confidence: 99%
“…The seasonal monsoon winds lead to coastal upwelling along the western margins of the Arabian Sea and the Bay of Bengal (Currie et al 1973;Shankar et al 2002). The intense upwelling in the Arabian Sea feeds nutrients to its surface waters, making it one of the most productive oceanic regions (Prasanna Naqvi et al 2006 and references therein). The deep waters of the Arabian Sea are composed of waters from south of the Equator and marginal seas like the Red Sea and the Persian Gulf (Shetye et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, denitrification in anoxic water bodies has a large isotope effect of ∼ −25 ‰ (e.g., Brandes et al, 1998; Voss et al 2001). To date, little is known about the isotope fractionation of anammox in the water column, but it is generally assumed that anammox, just like denitrification, coincides with considerable, possibly similar, isotope fractionation (Naqvi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%